Enhancing Science Process Skills through Conceptual Teaching and Learning Related to Water-Savings and Natural Events Concept - Neni Hermita; Mahmud Alpusari; Eva Astuti Mulyani; Anggi Paura; Herliana Herliana (Universitas Riau, 2020)
This study aims to enhance science process skills (SPS) through contextual teaching and learning (CTL). This research method used the Quasi-Experiment None-equivalent Pretest-Posttest Design Group. This research was conducted at SDN 002 Ujung Batu with a sample of 54 students. The results obtained that the science process skills of students who learn with the CTL model are better and have more significant improvement than those who learn with conventional models. The experiment group obtained a posttest score with an average of 90.71, while the control group obtained an average of 51.42. N-gain of students' SPS in the experiment group is 0.56 (medium category) higher than the control group that is 0.24 (low category). These indicate that the CTL model can enhance the SPS of fifth-grade elementary school students in the saving-water and natural events concept.